Transfer of Knowledge in Twentieth-Century Muslim Ethiopia: The Library of al-Šayḫ al-Ḥāǧǧ Ḥabīb from Wällo - Hernández López, Adday (Aethiopica, 2017)
Although Muslims in Ethiopia are a large part of the total population, nevertheless, their literary tradition and their cultural heritage have, until the present, hardly been studied by the academic community. The present article aims to shed light on the Islamic manuscript tradition in Ethiopia in the late nineteenth and early twentieth centuries by focus-ing on several codices owned by al-Šayḫ Ḥabīb, a renowned scholar and respected walī from Wällo, in north-eastern Ethiopia.